O desequilíbrio do contrato por adesão no Código Civil brasileiro - Miyazato, Sheila Keiko Fukugauchi (2021)
The unsettling inquiries about the legal phenomenon of contracts by adhesion are not current, torrential debates have occurred for decades discussing their correct position in legal science. In Brazil, the article was inserted, firstly, only in consumer articles by the Consumer Defense Code, in 1990, and, only in 2002, by the Civil Code, which seems recent compared to discussions in Europe, since the beginning of the century XX. The Civil Code of 2002 was the first brazilian Civil Code to consider the contract by adhesion and it was done very narrowly in just two articles to deal generically with the subject, which brings us great losses, in addition to the confusions, of course. We will start by punctuating its legal bases and, subsequently, evolution and trends, general aspects, legal nature and positive law in Brazil, with special emphasis on the dialogue of sources between Civil Code and Consumer Defense Code, regarding the definition of the contract by adhesion and regarding the matter of contractual abusiveness. The unfair clauses of the Consumer Defense Code are used as an interpretative and integrative vector. The imbalance between parties is a core issue affecting the contract by adhesion and the subject develops in the aspect of abusiveness, compromises contractual bilaterality, a subject linked to the principle of contract balance. In this reasoning, we will seek to point out the effectiveness of the mechanisms for equalizing the contractual relationship in the contract by adhesion